2020
DOI: 10.2478/udi-2020-0008
|View full text |Cite
|
Sign up to set email alerts
|

Konsekwencje suburbanizacji dla miast i stref podmiejskich w świetle literatury krajowej i zagranicznej

Abstract: AbstraktArtykuł obejmuje analizę wpływu suburbanizacji na sferę społeczną, kulturową, funkcjonalno-przestrzenną, gospodarczą oraz na środowisko naturalne Polski. Opracowanie rozpatruje konsekwencje zjawiska z perspektywy suburbiów oraz miasta centralnego. Dla celów niniejszej publikacji dokonano analizy publikacji krajowych opisujących badania procesu w miastach Polski oraz publikacji zagranicznych. Pozycje anglojęzyczne obejmowały badaniami skutki suburbanizacji w miastach Europy, Azji, Ameryki Północnej, Ame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 9 publications
0
3
0
2
Order By: Relevance
“…1, it may be concluded that highly developed and industrialized countries (EU Member States, Japan) witnessed an appreciable reduction in the area of agricultural land (by approximately 3-5%) over the study period, because it was often converted for service and industrial uses (for instance to establish new businesses) and due to the development of infrastructure. The EU provides financing for the development of non-agricultural rural activities and witnesses a rapid suburbanization of rural areas (Koj, 2020;Stelmaszewska, 2020). In turn, it is the opposite for less developed and less industrialized countries, except for Argentina.…”
Section: Volume Of Productive Inputsmentioning
confidence: 99%
See 1 more Smart Citation
“…1, it may be concluded that highly developed and industrialized countries (EU Member States, Japan) witnessed an appreciable reduction in the area of agricultural land (by approximately 3-5%) over the study period, because it was often converted for service and industrial uses (for instance to establish new businesses) and due to the development of infrastructure. The EU provides financing for the development of non-agricultural rural activities and witnesses a rapid suburbanization of rural areas (Koj, 2020;Stelmaszewska, 2020). In turn, it is the opposite for less developed and less industrialized countries, except for Argentina.…”
Section: Volume Of Productive Inputsmentioning
confidence: 99%
“…Na podstawie danych przedstawionych w tabeli 1 można wskazać, że w państwach wysoko rozwiniętych i uprzemysłowionych (kraje UE, Japonia) wielkość użytkowanej rolniczo ziemi odczuwalnie zmniejszyła się (o ok. 3-5%) w analizowanych latach, ponieważ często była ona przekształcana na potrzeby sektora usługowego i przemysłowego, chociażby dla nowych przedsiębiorstw oraz ze względu na rozwój infrastruktury. W UE występuje dofinansowanie na rozwój działalności pozarolniczej na obszarach wiejskich oraz szybko postępująca suburbanizacja terenów wiejskich (Koj, 2020;Stelmaszewska, 2020). Z kolei w krajach mniej rozwiniętych i słabiej uprzemysłowionych miała miejsce sytuacja odwrotna, z wyjątkiem Argentyny.…”
Section: Volume Of Productive Inputsunclassified
“…Z kolei Mielczarek (2011) wyróżniła trzy aspekty, na które oddziałuje proces suburbanizacji: środowiskowy, ekonomiczno-przestrzenny i społeczny. Jak podkreśla Stelmaszewska (2020), poszczególne zjawiska towarzyszące suburbanizacji (m.in. powstawanie nowych, rozdrobnionych osiedli mieszkaniowych, przypadkowość lokalizowania poszczególnych funkcji) mogą prowadzić do kolizji interesów użytkowników przestrzeni.…”
Section: Pojęcie Suburbanizacjiunclassified
“…The increased demand for housing units and apartments is mostly evident in large and dynamic municipalities and in their immediate surroundings (Stelmaszewska, 2020). This trend is relatable to the ongoing and steady path of urban development (Szymańska & Biegańska, 2011).…”
Section: Determinants Of Changes In the Primary Real Estate Market Un...mentioning
confidence: 99%